The effect of convenience and self-efficacy on the satisfaction of learning management system usage - Zulherman, Zulherman; Mansor, Abu Bakar Ahmad; Kulgemeyer, Christoph (Institute of Advanced Engineering and Science, 2025)
Universities widely use the learning management system (LMS) technology due to its flexibility and ease of use for lecturers when managing online learning with the LMS. The primary determinant of success is the admittance of students utilizing this technology based on the LMS. However, institutions have challenges when utilizing LMS systems. The study aims to evaluate the factors that impact student satisfaction (SS) when using the LMS. The study methodology employs the Delone McLean model technique, incorporating the elements of convenience (Co) and self-efficacy (SE) into the survey. Data was gathered from a sample of 178 undergraduate students. The data analysis conducted using structural equation modeling (SEM) partial least squares (PLS) entailed the testing of six hypotheses. The results found that only three hypotheses were supported: information quality (IQ) and system quality (SQ) had a positive impact on SS. Student satisfaction also harmed the use of LMS (LU). This research contributes to the knowledge that internal and external factors of the LMS system also play an important role in the satisfaction of LMS usage.